THE LOGIC OF BINCAR-BONOM AND STRUCTURALISM ANALYSIS ON ROOM ARRANGEMENT OF DWELLING IN MANDAILING - Cut Nuraini; Hibnul Walid; Meyga Fitri Handayani (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2018)
The structure on an idea of Singengu ancestor about Datu (Creator) which is gives tondi (spirit/soul) through direction of sun movement has established the logic of Bincar (sunrising direction) and Bonom (sunsetting direction). The logic of Bincar-Bonom with the axis point has been manifests in the form of myths about relationships between Datu (Creator/God), King (Datu’s agent in the world) and the ancestors which also form the structure of abstract space namely Bincar and Bonom. The structure of abstract space namely Bincar-Bonom in the next steps has transformed concretely on architectural phenomena as a place on room arrangement. Bincar-Bonom in the context of structural concept is transformed in to room arrangement phenomenon concretely which has arrange the setting of bedroom for parent in the direction of Bonom and bedroom for son in the direction of Bincar with family room in the midle of it as axis point.